Atención farmacéutica en la bibliografía nacional e internacional - Elodie Ouadahi (Fundación Pharmaceutical Care España, 2022)
Assessing the pharmaceutical care provision to suspected COVID‑19 patients in community pharmacies: a simulated patient study. Karout y col. BMC Health Services Research (2022) 22:467. https://doi.org/10.1186/s12913-022-07870-1 The Quality of Counseling for Headache OTC Medications in German Community Pharmacies Using a Simulated Patient Approach: Are There Differences between Self-Purchase and Purchase for a Third Party? Langer, B. y Kunow, C. The Scientific World Journal, vol. 2022, ID del artículo: 5851117, 14 pag. https://doi.org/10.1155/2022/5851117 Opioid treatment program prescribing of methadone with community pharmacy dispensing: Pilot study of feasibility and acceptability. Brooner, R K. y col. Drug and Alcohol Dependence Reports, Volume 3, June 2022, 100067, ISSN 2772-7246 https://doi.org/10.1016/j.dadr.2022.100067